"If they misbehaved, we took a stick to discipline them": Refugee mothers' struggles raising children in the United States. Issue 2 (23rd October 2019) - Kohli, Hermeet K.; Fineran, Susan
Abstract: Although there are compelling examples of stress put upon refugee families, there is little systematic attention placed upon how the refugee women themselves view child‐rearing. In this exploratory research, refugee women's narratives concerning their understanding and perceptions of child‐rearing in the United States are studied. Seventeen refugee women raising children living in the Greater Portland region in Maine were interviewed. While resettling in the United States, the participants shared being overburdened by the loss of social structures that supported their parenting beliefs and strategies back home. They perpetually encounter cultural conflicts in the United States that result in a continuous process of contradictory interpretations and negotiations while rearing and disciplining children. Recommendations are provided for service providers working with this population. Professionals have to be cognizant of the hierarchical decision‐making and retributive strategies used by refugee families when disciplining children. Tools, that is, explaining, teaching, and rewarding children for coping with parenting challenges without resorting to punitive discipline methods can be introduced to refugee families. Professionals need to focus on providing refugee families with basic needs and addressing social and emotional challenges so that they can better integrate with the new communities as they rebuild their lives.